النظام القانوني للمرصد الوطني للمجتمع المدني في الجزائر - محمد الطاهر قد العود; أيمن حفصي (My University, 2024)
Summary The National Observatory for Civil Society Is an advisory body to the President of the Republic, established under Article 213 of the 2020 constitutional amendment. In implementation of this article, Presidential Decree 21/139 was issued, which defined the composition, organization, operation, and tasks of the observatory. The latter serves as a framework for dialogue, consultation, suggestion, and foresight on all issues related to civil society. It also contributes to promoting national values and democratic practices and collaborates with other institutions in achieving national development goals. Therefore, the National Observatory for Civil Society serves as a link between civil society and the state, aiming to enhance good governance and the rule of law. ...................... الملخص يعد المرصد الوطني للمجتمع المدني هيئه استشارية لدى رئيس الجمهورية، تم استحداثه بموجب المادة 213 من التعديل الدستوري 2020 وتجسيدا لهذه المادة صدر المرسوم الرئاسي 21 / 139، الذي حدد تشكيلة وتنظيم والسير ومهام المرصد، حيث يعد هذا الأخير إطار للحوار والتشاور والاقتراح والاستشراف في كل المسائل المتعلقة بالمجتمع المدني، كما يساهم في ترقية القيم الوطنية والممارسة الديمقراطية ويشارك مع المؤسسات الأخرى في تحقيق أهداف التنمية الوطنية، بناءا على ما سبق فإن المرصد الوطني للمجتمع المدني يعتبر حلقه وصل بين المجتمع المدني والدولة، وذلك من اجل تعزيز الحكم الراشد ودولة القانون. ............................. Résume Le Observatoire national de la société civile est un organe consultatif auprès du président de la République, créé en vertu de l'article 213 de la réforme constitutionnelle de 2020. Pour concrétiser cet article, le décret présidentiel 21/139 a été publié, définissant la composition, l'organisation, le fonctionnement et les missions de l'Observatoire. Ce dernier constitue un cadre de dialogue, de consultation, de proposition et de prospective sur toutes les questions relatives à la société civile, contribuant à promouvoir les valeurs nationales, la pratique démocratique et à participer avec d'autres institutions à la réalisation des objectifs de développement national. Ainsi, l'Observatoire national de la société civile est un lien entre la société civile et l'État, dans le but de renforcer la gouvernance éclairée et l'État de droit.